Characterization of the human gut virome in metabolic and autoimmune diseases - Kosuke Fujimoto; Daichi Miyaoka; Satoshi Uematsu (Inflammation and Regeneration, 2022)
Abstract The intestinal microbiome is dominated by bacteria and plays a pivotal role in the occurrence and development of disease, including several metabolic and autoimmune disorders. While intestinal viral communities, primarily made up of bacteriophages, are also thought to play a role in disease pathogenesis in the gastrointestinal tract, they have received much less attention than intestinal bacteria. Thus, there is limited information about the relationship between bacteriophages and disease. This review explores a potential role for the intestinal viral microbiome in various metabolic and autoimmune diseases.